2013
DOI: 10.1212/wnl.0b013e3182a2ca34
|View full text |Cite
|
Sign up to set email alerts
|

Triple dissociation of attention networks in stroke according to lesion location

Abstract: More than half of all stroke patients can be expected to have a lesion location classifiable into 1 of the 3 principal attention networks. Our results have potential implications for therapy personalization in focal brain diseases including stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 41 publications
2
40
2
5
Order By: Relevance
“…Several fMRI studies have shown that orienting tasks activate areas of the superior temporal lobe and the temporal–parietal junction . Evidence from lesion studies has revealed that impairments in orienting accompany lesions of the right pulvinar and temporoparietal cortex and the superior temporal lobe . In the present study, we found no differences in the orienting network between the CT group, the non‐CT group, and the healthy controls.…”
Section: Discussioncontrasting
confidence: 63%
“…Several fMRI studies have shown that orienting tasks activate areas of the superior temporal lobe and the temporal–parietal junction . Evidence from lesion studies has revealed that impairments in orienting accompany lesions of the right pulvinar and temporoparietal cortex and the superior temporal lobe . In the present study, we found no differences in the orienting network between the CT group, the non‐CT group, and the healthy controls.…”
Section: Discussioncontrasting
confidence: 63%
“…This effect is in keeping with studies on cueing effects [38] that show that incongruent spatial information carried by a cue and a target could lead to a slower response to the target, thus enhancing the interaction of the processing of the cue and target in the brain, especially under short stimulus onset asynchronies. The interdependence between components is also supported at the neural level: Rinne and colleagues [78] reported anatomical dependency of internetwork interactions and, to a lesser extent, overlap in a cohort of stroke patients, showing how lesions to right frontoparietal regions could modulate the interactions among the three attentional components.…”
Section: Discussionmentioning
confidence: 94%
“…Differential effects of lesions upon the different attention networks have been confirmed in neurological patients (Hu et al, 2013;Rinne et al, 2013;Xu et al, 2010). Attention deficits are among the most commonly observed cognitive impairments after stroke Robertson and Murre, 1999) and are known to severely affect rehabilitation (McDowd et al, 2003) resulting in a poorer outcome (Murphy and Corbett, 2009).…”
Section: Clinical Relevance Of Attention Deficits and Tdcs As A Neuromentioning
confidence: 94%